2020
DOI: 10.17344/acsi.2019.5720
|View full text |Cite
|
Sign up to set email alerts
|

Sulfonamide Derived Esters: Synthesis, Characterization, Density Functional Theory and Biological Evaluation through Experimental and Theoretical Approach

Abstract: A series of new solid esters was synthesized by using greener chemistry strategy involving simple reaction of an alcohol with sulfonamide ligand. Characterization study of these methyl (1), ethyl (2) isopropyl (3) and n-butyl (4) ester of 4-((4-chlorophenylsulfonamido)methyl)cyclohexanecarboxylic acid was done by using FTIR, NMR mass spectrometry and X-ray crystallography. The compounds were optimized with Gaussian software according to basis set B3LYP/6-31G(d,p) and their different parameters related to struc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Docking results and analysis with graphical representation were determined with the help of MOE and the discovery studio visualizer. [ 33 , 40 ] For interactional analysis of Spike Glycoprotein of SARS‐Cov2 and 55 heterocyclic compounds, The protein was retrieved from the Protein Data Bank from the PDB ID of 6VXX. The synthetic heterocyclic compunds were converted into PDB format from conical SMILES by utilization of OpenBable.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Docking results and analysis with graphical representation were determined with the help of MOE and the discovery studio visualizer. [ 33 , 40 ] For interactional analysis of Spike Glycoprotein of SARS‐Cov2 and 55 heterocyclic compounds, The protein was retrieved from the Protein Data Bank from the PDB ID of 6VXX. The synthetic heterocyclic compunds were converted into PDB format from conical SMILES by utilization of OpenBable.…”
Section: Methodsmentioning
confidence: 99%
“…2D ligand enzyme interaction was checked with the help of the ligand interaction module of MOE. Docking results and analysis with graphical representation were determined with the help of MOE and the discovery studio visualizer [33,40] . For interactional analysis of Spike Glycoprotein of SARS‐Cov2 and 55 heterocyclic compounds, The protein was retrieved from the Protein Data Bank from the PDB ID of 6VXX.…”
Section: Methodsmentioning
confidence: 99%
“…55,56 Docking studies Docking studies for the compounds 5-8 were performed with online free soware according to the reported method. [57][58][59][60] The AChE and BChE with PDB codes 1EVE and 1P0I, respectively were utilized for docking purposes. The 2D ligand enzyme interactions were established via the ligand interaction module.…”
Section: Acetylcholine and Butyrylcholine Esterase Inhibitionmentioning
confidence: 99%
“…All calculations were carried out with 6-31G(d,p) basis set [17,18]. During optimization with DFT, the input file was taken from the XRD data of synthesized compound (where applicable) and matched with the experimental data via DFT studies [19,20] .…”
Section: Density Functional Theorymentioning
confidence: 99%